THE STUDY OF JARGON USED IN CAPOEIRA SENZALA UNIVERSITAS BRAWIJAYA GROUP - SAPUTRA, SANDY (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study is designed to figure out what the jargons used by Capoeira Senzala Universitas Brawijaya group are and what the meanings of jargon used by Capoeira Senzala Universitas Brawijaya group are. It is conducted not only to understand but also to describe the application of the jargons used by Capoeira Senzala Universitas Brawijaya group. The data sources are the members and the instructors of this group. has found out 40 jargons used by Capoeira Senzala Universitas Brawijaya group. Jargon is classified into two terms, namely lexical term consisting of 12 terms and technical terms which consist of 28 terms used by Capoeira Senzala Universitas Brawijaya group. Moreover, the meanings and the usages are significant in communication. It can be concluded that jargons used by Capoeira Senzala Universitas Brawijaya have their own specific meaning which can be understood by people in that group community or group.   Key words: jargon, Capoeira, Senzala, Capoeira Senzala, Universitas Brawijaya, lexical term, and technical term.